A reflection on the musealization process: the intangible heritage in the museal spaces - de Jesus, Priscila Maria (Edições Universitárias Lusófonas, 2014)
This article aims to raise, questions about the musealization of intangible heritage and the use of new technologies in the exhibition process. Through an approach that seeks to bring the history of museums, this article makes an inquiry about the social role of museums in bringing visitors issues that permeate the reality of the social group in which it is inserted. Keywords: musealization, Intangible Heritage, Orality, New Technologies.